2007
DOI: 10.2174/138161207782023757
|View full text |Cite
|
Sign up to set email alerts
|

Non-Lethal Polypeptide Components in Cobra Venom

Abstract: Snakes from several genera (mostly from Naja genus) belonging to the Elapidae family are usually named cobras. The effect of cobra bites is mainly neurotoxic. This is explained by the presence of highly potent alpha-neurotoxin in their venoms. The other two highly toxic components of cobra venoms are cytotoxins and phospholipases A(2). These three types of toxins constitute a major part of cobra venom. They have attracted the attention of researchers for many years and have been very well studied and thoroughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 108 publications
2
9
0
1
Order By: Relevance
“…Indeed, CRISP isolated from various venoms blocks L-type of calcium and cyclic nucleotide gated channels, that may harm the victims [16,17]. However, experimental treatment of mice and insects with these proteins yielded no toxic effects [18]. Our studies with an avian embryonic model confirmed the lack of toxicity of snake venom CRISP, since ES-CRISP in doses up to 40 μg was harmless to quail embryos, which are very sensitive to exogenous toxins.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Indeed, CRISP isolated from various venoms blocks L-type of calcium and cyclic nucleotide gated channels, that may harm the victims [16,17]. However, experimental treatment of mice and insects with these proteins yielded no toxic effects [18]. Our studies with an avian embryonic model confirmed the lack of toxicity of snake venom CRISP, since ES-CRISP in doses up to 40 μg was harmless to quail embryos, which are very sensitive to exogenous toxins.…”
Section: Discussionsupporting
confidence: 64%
“…The biological activity of snake venom CRISPs is still not fully understood; some were characterized as blockers of L-type calcium channels [16] and cyclic nucleotide gated channels [17]. Although ex vivo, CRISPs block rat arterial smooth muscle contraction [16], they appear to belong to the non-toxic components of snake venoms, because they have no toxic effects on mice or insect [18]. Recent studies showed that CRISP isolated from cobra venom, activates endothelial cells as inferred from the increased expression adhesion molecules (VCAM-1 and ICAM-1) and E-selectin [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several Elapidae snake venoms with neurotoxic activity, such as the cobras (Elapidae), also contain proteins that activate or inhibit the hemostatic system (Utkin and Osipov, 2007; Osipov et al, 2010). For instance, a metalloprotease enzyme capable of activating factor V was described in the venom of Naja naja oxiana (Gerads et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Snake venoms are complex mixtures of peptides and proteins possessing different types of biological activity (1). Recent proteomic studies showed that, depending on the snake species, each venom may contain from several tens (2) to several hundred (3, 4) proteins.…”
Section: Introductionmentioning
confidence: 99%